Neurosurgery in a Case of Suspected Prion Disease: Challenges Faced - Abdul Salam, Anooja; Dubey, Arvind (Indian Journal of Neurosurgery, 2020)
This report refers to a rare case of a patient with suspected prion disease and the steps taken for the infection control measures in postsurgical management of a large sphenoid wing meningioma. Stringent measures are needed to prevent the transmission of Creutzfeldt–Jakob disease (CJD) to other patients or healthcare workers. The main concern, especially in a neurosurgical case, is the handling of highly infective tissue and hence the higher risk of disease transmission. This report provides guidance based on the experience in this case, as an aid to similar surgeries.
Keywords: central sterilizing department; Creutzfeldt–Jakob disease; prion disease